Clostridioides difficile on dairy farms and potential risk to dairy farm workers. (June 2021) - Redding, Laurel; Huang, Elizabeth; Ryave, Jacob; Webb, Terry; Barnhart, Denise; Baker, Linda; Bender, Joseph; Kristula, Michaela; Kelly, Donna
Abstract: Clostridioides difficile causes severe colitis in people and is a significant enteric pathogen in many species of animals, including swine, horses, and potentially cattle. C. difficile is shed in feces, and transmission occurs horizontally via the fecal-oral route. Livestock has been suggested as a potential reservoir for C. difficile, and while studies have shown that swine and farm workers can be colonized with identical clones of C. difficile, the zoonotic transmission of C. difficile from livestock to people has not been definitively demonstrated. The goal of this study was to determine whether dairy calves and dairy farm workers harbored genetically similar isolates of C. difficile . First, we validated a glove juice protocol for detecting C. difficile on farm workers' hands. We then visited 23 farms and collected 1) fecal samples from 92 dairy calves, 2) hand rinsates from 38 dairy farm workers, and 3) fecal samples from five of the dairy farm workers who were willing to submit them. All samples underwent anaerobic culture and qPCR to detect C. difficile . C. difficile was detected on 15 of the farms (65.2%, 95% confidence interval (CI) 42.7%–83.6%) and in 28 calves (30.4%, 95% CI 21.2–40.9%) but in none of the hand rinsates or human fecal samples. Thus, the zoonotic transmission of C. difficile on dairy farms could not be demonstrated, and dairy farmers did not appear to be at increased risk of acquiring C. difficile via the fecal-oral route. Graphical abstract: Image 1 Highlights: Clostridoides difficile was isolated from dairy calves on 15/23 (65.2%) dairy farms and in 28/92 (30.4%) dairy calves. C. difficile was not detected on the hands of 38 dairy farm workers or in the stool of five of the same workers. While zoonotic transmission of C. difficile from calves to farm workers cannot be ruled out, it does not appear likely.